Pengaruh Likuiditas Dan Solvabilitas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Pemoderasi - Ameliani, Findia; Akhmadi, Akhmadi (GEMA EKONOMI, 2023)
This study aims to examine the effect of liquidity and solvency on firm value moderated by profitability in the metal and allied product sector companies. The approach used in this research is a quantitative approach. The sample in this study were 13 companies in the metal and allied product sector that were registered on the IDX in the period 2015 - 2021. The research data is secondary data which is then processed using a panel regression analysis technique. The results showed that liquidity did not have a significant effect on the value of companies in the metal and allied product sector, while solvency proved to have a significant effect on the value of companies in that sector. Profitability apart from being a predictor of firm value can also moderate the effect of liquidity and solvency on firm value.